Sprzedaż biometanu po stałej cenie zakupu jako instrument prośrodowiskowej regulacji sektorowej - Kosiński, Eryk; Trupkiewicz , Marcin (PRAWO i WIĘŹ, 2025)
The authors analyse the changes made to Poland’s Renewable Energy Sources Act regarding the support system for biomethane, in relation to the implementation of the RED II Directive and the EU hydrogen and gas decarbonisation package. In the first part of the study, they describe the basis of pro-environmental, sector-specific regulation, particularly in the gas industry, and the potential for using biomethane to decarbonise this sector. They then analyse changes in European policy and legislation relating to biomethane, as set out in the Polish National Energy and Climate Plan. The final section of the paper focuses on the key instrument for supporting biomethane in Poland: the sale of biomethane at a fixed purchase price. In this regard, they analyse the legal framework for this instrument, the procedure for obtaining support, the level of the fixed purchase price, the support period, and the rules for settling accounts with the entity paying the state aid.